Radical sanation of a marriage Canons 1161-1165 - Mendonça, Augustine 1941- (2006)
Recently I attended the wedding of a cousin that was co-officiated by a priest ( not myself) and a rabbi. The wedding took place at a banquet facility quite distant from the parish my cousin attends. The priest accepted the couple's vows. The priest was not from the diocese where the wedding took place. Upon further inquiry, it came to my attention that the priest is not one to concern himself overmuch about the niceties and necessities of canon law. I am seeking the wise canonical counsel as to the best way in which I should proceed. It is my suspicion that no dispensations were granted. I wish neither to embarrass the priest nor to disturb my cousin and her new husband. Would it be possible for me to inquire of the chancellor of the diocese where the wedding took place as to whether any dispensations had been granted. If none were, would I be able to request a sanatio in radice on behalf of the couple and see that the appropriate notations were made?
Keywords: Katholische Kirche; Eherecht; Sanatio in radice; Religion; Verschiedenheit